Analisis Penerapan Sistem dan Prosedur Akuntansi dalam Pengelolaan Dana Desa: (Studi Kasus Desa Geliting, Kecamatan Kewapante, Kabupaten Sikka) - Aldolfus Lotak; Maria Nona Dince; Wihelmina Maryetha Yulia Jaeng (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze the application of accounting systems and procedures in managing Village funds. This research was conducted in Geliting village, Kewapante District, Sikka Regency. This research data was obtained from several data collection techniques, namely through observation and interviews. The results of this research indicate that the accounting system and procedures in managing village funds in Geliting Village are in accordance with Permendagri No. 113 of 2014 which includes: (1) In the planning stage, the Geliting village government involves the community to play an active role in the village fund planning process. (2) In the implementation stage, the village government carries out all programs mutually agreed between village officials and the community which prioritizes community needs. (3) The administration stage, in the form of recording transactions, both receipts and expenditures, in the general cash book, tax assistant cash book and bank cash book. (4) Reporting stage, in the form of submitting a report on budget realization which is carried out in two stages. (5) Accountability stage, in the form of the obligation of the village government to be accountable for budget realization reports to the central district government. However, at the reporting stage in the form of submitting reports on budget realization, delays often occur for several years.